1993
DOI: 10.1007/bf02244338
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose and human memory

Abstract: As it has been suggested that blood glucose might play a role in the action of some cognitive enhancing drugs, the influence of glucose containing drinks on human memory was examined. In a double-blind study the influence was examined of a drink containing 50 g glucose, or a placebo, on the ability to recall a word list. There was a significant correlation between blood glucose values and the number of words recalled. Those whose blood glucose levels were increasing remembered significantly more words than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
67
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 25 publications
16
67
5
Order By: Relevance
“…A recent meal may interact with the impact of arousal on blood glucose as well as with the effect of further glucose intake (Martin & Benton, 1999). Moreover, fasting has been associated with enhanced speed of performance on memory tasks in some studies (Benton & Owens, 1993;Green et al 1997a), but poorer recall levels in others (Martin & Benton, 1999).…”
Section: Mechanistic Implicationssupporting
confidence: 42%
“…A recent meal may interact with the impact of arousal on blood glucose as well as with the effect of further glucose intake (Martin & Benton, 1999). Moreover, fasting has been associated with enhanced speed of performance on memory tasks in some studies (Benton & Owens, 1993;Green et al 1997a), but poorer recall levels in others (Martin & Benton, 1999).…”
Section: Mechanistic Implicationssupporting
confidence: 42%
“…The findings of this study should be treated with caution, as it is difficult to determine on the basis of the results presented by the authors whether glucose ingestion per se has influenced reaction time, or whether some other factor(s) known to influence blood glucose concentration (such as stress hormone release) in fact contributed to the reported findings. Other aforementioned studies by this group have also used a similar, questionable data analysis strategy in concluding that glucose influences verbal episodic memory (Benton and Owens, 1993) and attention performance .…”
Section: Methodological Issuesmentioning
confidence: 43%
“…However, a number of studies have failed to observe a glucose enhancement effect in healthy young adults for tests of verbal episodic memory in which memory materials were encoded under single task conditions (Azari, 1991;Benton and Owens, 1993;Hall et al, 1989;Manning et al, 1997;Scholey et al, 2001;Scholey and Kennedy, 2004;Winder and Borrill, 1998). In addition, further studies that have observed a glucose enhancement effect in the domain of verbal episodic memory under single task conditions in healthy young adults have reported an improvement only for primacy and/or recency items Messier et al, 1998), or when a dichotic listening paradigm is employed (Parker and Benton, 1995).…”
Section: Divided Attentionmentioning
confidence: 44%
“…Reaction time tasks appear to be sensitive to changes in blood glucose. Following a glucose drink, blood glucose level correlated with improved decision time (18). Poorer performance was associated with slower removal of glucose from the blood.…”
Section: Effects Of Glucose On Cognition and Moodcontrasting
confidence: 39%
“…Recovery from nadir and rising levels of blood glucose were associated with better recall than were falling blood glucose levels (18,19). The effect of 50 g glucose on memory for trigrams depends on the initial blood glucose levels of the subject (8) (Fig.…”
Section: Effects Of Glucose On Cognition and Moodsupporting
confidence: 38%